Production Scheduling Analysis To Minimize Inject–Blow Production Makespan on PT.XYZ Using Differential Evolution Algorithm Method - Dzati Fauziyah; Tedjo Sukmono (Procedia of Engineering and Life Science, 2022)
This study discusses the problem of job-shop scheduling at one of the well-known mineral water companies in Indonesia. This company produces a number of products in several types with different routes from each other. However, in reality, the effectiveness of production lies in the range of 54.8%–69.2%, so it is still far from running time production where the expected target is 80% for inject and 90% for blow. Where production scheduling is a complex problem so it takes the right method to get the optimal solution for these problems. The research method used is the differential evolution algorithm method, where this method aims to minimize the makespan value (total completion time of all jobs) on the job-shop production route so as to obtain optimal scheduling results and improve the existing system. Scheduling obtained through the differential evolution algorithm method produces a makespan value of x minutes, while the company's schedule has a makespan value of y minutes. So that the proposed scheduling results in a decrease of x% compared to company scheduling.